Stability of the Unit Movement Depending on the Agricultural Operations Performed on Slopes - Musurmonov Azzam Turdievich; Utaganov Khusan Baimatovich; Ochildiyev O‘Tkir Ollanazarovich; Khazratkulov Shermat Azamovich; Raxmatxodjaev Sherzod Turg‘Unboevich (American Journal of Biodiversity, 2025)
The article outlines the dependence of the degree of mutual influence of an agricultural implement and a tractor, taking into account the factors affecting the balance of the tractor, and lists the types of maintaining the direction of movement of the unit during an agricultural operation.